Perancangan Sistem E-Learning Di Sekolah Menengah Kejuruan Dharma Bhakti 4 Kota Jambi: e-learning - WARDANI, MUHAMMAD; Ni Luh Ayu Yaticha; Tiko Nurhaliza; Akwan Sunoto (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2026)
SMK Dharma Bakti 4 Kota Jambi is one of the vocational secondary education institutions that has been conducting learning activities using conventional methods, namely face-to-face learning in classrooms. With the development of information technology, the demand for innovation in the learning process has increased, especially to support the flexibility and sustainability of teaching and learning activities. Therefore, the development of an E-Learning system is a relevant solution to be implemented. This study focuses on the design and development of an E-Learning platform designed to facilitate the distribution of teaching materials by teachers and make it easier for students to access materials, complete assignments, and take evaluations such as midterm and final exams online. This system was developed using the PHP programming language and MySQL database with the aim of creating a more effective, structured, and accessible learning service. The results of the development show that the implementation of E-Learning can improve the efficiency of the learning process, especially in conditions that require distance learning. In addition, this platform also provides features for delivering announcements and processing grades, which help facilitate academic administration at SMK Dharma Bakti 4 Jambi City. Thus, this E-Learning system is expected to be a sustainable supporting tool in improving the quality of learning in the school environment. Keywords: Design; System; E-learning; Vocational High School; MySQL